2023
DOI: 10.1111/aogs.14527
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and gestational age in the Faroe Islands: A comparison between birthweight and gestational age in the Faroe Islands and other Nordic countries

Abstract: Introduction This study aimed to examine Faroese infants' birthweight and gestational age in 2010–2019 and compare these findings with other Nordic countries. Risk factors for high birthweight among Faroese infants were also investigated in this study. Material and methods All singleton liveborn infants registered in the Faroese Birth Registry in 2010–2019 were included in the study (n = 6121). A comparison was made with data on birthweight and gestational age from Denmark, Iceland, Norway, and Sweden. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…This is in line with studies from the United States (Donahue et al, 2010;Morisaki et al, 2013;Oken, 2013) and South Korea (Hur, 2023). However, other countries have found either mixed results (Diouf et al, 2011) or an increase in birth weight across time (Ghosh et al, 2018;Olsen et al, 2023;Schack-Nielsen et al, 2006). A study by Sankilampi and colleagues (2013) shows an increase in mean birth weight in Finland between 1979Finland between -1983Finland between and 1996Finland between -2008 Our study complements this study and we assume that there is a higher mean birth weight between 1987-1996 than both time periods (1979-1983 and 1996-2008) as presented by Sankilampi and colleagues, with a following decline.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with studies from the United States (Donahue et al, 2010;Morisaki et al, 2013;Oken, 2013) and South Korea (Hur, 2023). However, other countries have found either mixed results (Diouf et al, 2011) or an increase in birth weight across time (Ghosh et al, 2018;Olsen et al, 2023;Schack-Nielsen et al, 2006). A study by Sankilampi and colleagues (2013) shows an increase in mean birth weight in Finland between 1979Finland between -1983Finland between and 1996Finland between -2008 Our study complements this study and we assume that there is a higher mean birth weight between 1987-1996 than both time periods (1979-1983 and 1996-2008) as presented by Sankilampi and colleagues, with a following decline.…”
Section: Discussionsupporting
confidence: 90%
“…The increase was still present after controlling for the increase in maternal age and decrease in smoking. A recent study from the Faroe Islands showed an increase of 93 grams in birth weight of singleton Faroese infants born between 2010-2019, although the same increase could not be found in other Nordic countries (Olsen et al, 2023). The authors suggest that this could possibly be explained by a larger proportion of infants born in gestational week 41 or later compared to the other Nordic countries, which possibly could relate to differences in the practice of labour induction (42 weeks and 0 days in Faroe Islands and 41weeks and 5 days in other Nordic countries).…”
Section: Introductionmentioning
confidence: 81%
“…The increasing birthweight trend observed in the first period (1999-2008) parallels with similar observations from other high income countries [6][7][8][9][10][11][12][13][14]17] including those from Croatia [15], Poland [40] and a regional database analysis from Hungary [33].…”
Section: Birthweight Trendssupporting
confidence: 83%
“…Given the strong association between birthweight and later chronic diseases, even small temporal changes in the distribution of term newborns' birthweights could be of utmost public health importance. Indeed, an upward birthweight trend was observed in several high income countries and regions (such as the United States (US) [6], Canada [6,7], the United Kingdom (UK) [8,9], Norway [10], Sweden [11], Denmark [12], France [13], Australia [14], Croatia [15], Poland [16], and the Faroese Island [17]) at the end of the last century. In contrast, a reverse trend was found in Japan [18,19] and the increase appeared to reverse in the US [20][21][22][23][24][25], China [26,27], Portugal [28], Norway [29,30], and Germany [31] after the 1990s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation